STRATEGI GURU PAI DALAM MENINGKATKAN MOTIVASI RELIGIOUS LEARNING BAGI SISWA SDN GUNUNG RANCAK SAMPANG: STRATEGI GURU PAI DALAM MENINGKATKAN MOTIVASI RELIGIOUS LEARNING BAGI SISWA SDN GUNUNG RANCAK SAMPANG - Mar waki (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2020)
ABSTRACT Teachers play an important role as educators in shaping the personality of their students. In this study, the PAI teacher's strategy was examined in enhancing religious learning motivation at Gunung Rancak 2 Elementary School in Gunung Rancak Village, Robatal District, Sampang Regency. The method uses qualitative research, the technique of data collection is done by observation, interviews and documentation with the research subjects of principals, teachers, and students of Gunung Rancak SDN 2. The results of this study are PAI teachers using strategies to improve Islam. religious motivation by explaining the purpose of learning, giving praise, giving gifts, giving punishment, using various methods, and giving encouragement on an ongoing basis. Factors that support the implementation of learning motivation include effective communication between teachers and students, and teaching materials that meet curriculum standards, and are supported by creating a conducive learning environment. The inhibiting factors encountered in increasing student motivation are low student interest in Islamic studies, lack of time allocation, lack of variation in student motivation, and differences in student abilities, non-optimal learning media, and family and social environment. Keyword: The Teacher Effort, Motivation, School